2016
DOI: 10.1371/journal.pone.0167149
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Matrix Metalloproteinases, Cytokines and Their Potential Role in the Development of Ovarian Cancer

Abstract: BackgroundOvarian cancer is the 5th most common cause of deaths in the women among gynecological tumors. There are many growing evidences that stress and other behavioral factors may affect cancer progression and patient survival. The purpose of this study is to determine the key role of matrix metalloproteinases (MMPs), and cytokines in the aggregation and progression of ovarian cancer.MethodologyStress variables (MDA, AGEs, AOPPs, NO), profile of antioxidants (SOD, Catalase, Vitamin E & A, GSH, GRx, GPx) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 39 publications
(34 reference statements)
0
15
0
Order By: Relevance
“…Evidence has been reported supporting the strong association between other members of the MMPs family and the occurrence, development, and metastasis of ovarian cancer ( 29 ). Qiu et al ( 13 ) found that the regulation of MMP-3 and MMP-2 expression is involved in the estradiol-induced migration and invasion of SKOV3 cells.…”
Section: Relationship Of Mmps With Ovarian Cancermentioning
confidence: 93%
“…Evidence has been reported supporting the strong association between other members of the MMPs family and the occurrence, development, and metastasis of ovarian cancer ( 29 ). Qiu et al ( 13 ) found that the regulation of MMP-3 and MMP-2 expression is involved in the estradiol-induced migration and invasion of SKOV3 cells.…”
Section: Relationship Of Mmps With Ovarian Cancermentioning
confidence: 93%
“…Although the role of TGFβ in ovarian cancer has been studied extensively, the function of TGFβ1 and TGFβ2 in exosomes remains to be explored to understand how these cytokines contribute to EMT in ovarian cancer. Matrix metalloproteinases (MMPs), especially MMP-2 and MMP-9, are proteases that are capable of degrading the extracellular matrix to support cancer cell escape from the primary tumor site and metastasis in ovarian cancer [ 23 25 ]. Recent studies report that tumor cell-derived exosomes promote an EMT phenotype through MMPs and TGFβ as cargo components [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs), a family of more than 20 zinc-dependent enzymes known to degrade extracellular matrix and basement membrane components [ 7 ], are not only a prerequisite for multiple steps of cancer development but also play important roles in cancer invasion and metastasis [ 8 ]. MMPs are correlated with ovarian cancer, with the levels of MMP-2, MMP-7 and MMP-9 elevated in ovarian cancer patients [ 9 10 ]. At genetic level, a number of studies have been carried out to assess the association between polymorphisms of MMPs and ovarian cancer risk [ 11 – 27 ], but the conclusions have been still conflicted and even contradictory.…”
Section: Introductionmentioning
confidence: 99%